X-ray powder diffraction pattern and crystal structure of AlCu4Y ternary compound. Issue 4 (29th October 2015) - Li, Degui; Qin, Ming; Liang, Liuqing; Qin, Changsheng; Jia, Chenzhong; Hu, Lei; He, Bing; Zeng, Lingmin
Abstract : The ternary compound of AlCu4 Y was synthesized by melting under argon atmosphere in the arc furnace. High-quality X-ray powder diffraction data of AlCu4 Y have been collected using a Rigaku SmartLab X-ray powder diffractometer. The Rietveld refinement results of the X-ray diffraction pattern for the AlCu4 Y compound showed that the AlCu4 Y is the hexagonal structure, space-group P 6/ mmm (No. 191) with a = 5.0658(1) Å, c = 4.1569(1) Å, V = 92.38 Å 3, Z = 1, and the density is 6.66 g cm −3, and the intensity ratio RIR is 1.96.